The Glasgow 'Deep End' Links Worker Study Protocol: A Quasi-Experimental Evaluation of a Social Prescribing Intervention for Patients with Complex Needs in Areas of High Socioeconomic Deprivation. Issue 1 (2017) - Mercer, Stewart W.; Fitzpatrick, Bridie; Grant, Lesley; Chng, Nai Rui; O'Donnell, Catherine A.; Mackenzie, Mhairi; McConnachie, Alex; Bakhshi, Andisheh; Wyke, Sally
Background: 'Social prescribing' can be used to link patients with complex needs to local (non-medical) community resources. The 'Deep End' Links Worker Programme is being tested in general practices serving deprived populations in Glasgow, Scotland. Objectives: To assess the implementation and impact of the intervention at patient and practice levels. Methods: Study design : Quasi-experimental outcome evaluation with embedded theory-driven process evaluation in 15 practices randomized to receive the intervention or not. Complex intervention : Comprising a practice development fund, a practice-based community links practitioner (CLP), and management support. It aims to link patients to local community organizations and enhance practices' social prescribing capacity. Study population : For intervention practices, staff and adult patients involved in referral to a CLP, and a sample of community organization staff. For comparison practices, all staff and a random sample of adult patients. Sample size : 286 intervention and 484 comparator patients. Outcomes : Primary patient outcome is health-related quality of life (EQ-5D-5L). Secondary patient outcomes include capacity, depression/anxiety, self-esteem, and healthcare utilization. Practice outcome measures include team climate, job satisfaction, morale, and burnout. Outcomes measured at baseline and 9 months. Processes : Barriers and facilitators to implementation of the programme and possible mechanisms through which outcomes are achieved. Analysis plan : For outcome, intention-to-treat analysis with differences between groups tested using mixed-effects regression models. For process, case-study approach with thematic analysis. Discussion: This evaluation will provide new evidence about the implementation and impact of social prescribing by general practices serving patients with complex needs living in areas of high deprivation.